Oxygen nonstoichiometry and thermodynamic characterization of Zr doped ceria in the 1573–1773 K temperature range1. Issue 12 (28th March 2015) - Takacs, M.; Scheffe, J. R.; Steinfeld, A.
<x xml:space="preserve">Abstract</x> The thermodynamics and defect chemistry of Zr4+-doped ceria is investigated and discussed in regards to the efficiency of solar thermochemical redox cycles.